Melalui Pendekatan Saintifik Metode Demonstrasi untuk Meningkatkan Penguatan Karakter Peserta Didik pada Tema Rekreasi di Kelas B1 TK Tuah Sakato Semester Genap TP. 2021/2022 - Erni Marlinda (Departement of Mathematics Education, 2022)
This study aims to obtain data and discuss the Scientific Approach of Demonstration Methods to Improve Character Strengthening of Students on Recreational Themes in Class B1 Tuah Sakato Kindergarten. Even Semester Tp. 2021/2022. This Classroom Action Research (CAR) was conducted in Group B1 at Tuah Sakato Kindergarten, Payobasung Village, East Payakumbuh District, Payakumbuh City. This classroom action research (CAR) was conducted in the even semester 2021/2022 academic year for three months from January to March 2022. This classroom action research (CAR) was carried out in two cycles with four stages of research, namely planning, implementation, observation, and reflection. As the subject in the research that the author did this was the students of Group B1 Kindergarten. Tuah Sakato, East Payakumbuh District, totaling 16 (sixteen) people. Data collection techniques that the author uses in this study are tests, observations, interviews, and discussions. The data collected in the observation activities from the implementation of the research cycle were analyzed descriptively by using the percentage technique to see trends that occur in learning activities. The results obtained from this study are teachers can improve learning outcomes and strengthen the character of students, with the following values. From the results of observations of characters in the Pre-cycle Category, 47% have not appeared and have started to appear 53%, then in Cycle I the category has not appeared 12%, starting from appeared 29% and succeeded as expected 59%, in Cycle II the category began to appear 12%, succeeded as expected 35% and succeeded very well 53%. For learning outcomes with the category of Very Good Success (BSB) Pre-cycle 0%, Cycle I 0% and in Cycle II increased 53%.